Umutina e Paresi : miradas memorialísticas e resistência - Cláudio Henrique Vieira (2021)
In the last decades, the advance of deforestation, agribusiness, the construction of the Belo Monte plant and the demarcation of indigenous lands have taken center stage in the long-standing battle between whites and native peoples. The people who survived recurrent genocides suffer from interference of all kinds: social, cultural, political, economic, religious and, in recent years, the growing exodus of young people to large urban centers. In this context, the series Amazônia Resiste appears, produced by Pública, an investigative journalism agency, which explores such issues in 12 episodes, giving protagonism to the indigenous people and their reports. This dissertation proposes to investigate the traces of individual and collective memories present in the images and stories of the characters of the Episodes: 03 - The Dream of Éder and 04 - Soy in the Paresi fashion, Umutina and Paresi ethnic groups, here named 'subjects in action'. Guided by the idea of territory and belonging, we will carry out a verboaudiovisual analysis seeking to understand the weaving memories of these peoples, attentive to the various crossings, affects and socio-technical dimensions of the series.Considering the cosmological aspect of indigenous cultures, discontinuities and temporalities present, we will adopt a before, a now and an after in allusion to the time of things. We understand that historical, chronological times - past, present and future -, agreed by westerners, do not apply in this memorialist approach.